MUC1 gene polymorphism in three Nelore lines selected for growth and its association with growth and carcass traits - Pablos de Souza, Fabio Ricardo [UNESP]; Maione, Sandra; Sartore, Stefano; Soglia, Dominga; Spalenza, Veronica; Cauvin, Elsa; Martelli, Lucia Regina; Zerlotti Mercadante, Maria Eugenia; Sacchi, Paola; Albuquerque, Lucia Galvão de [UNESP]; Rasero, Roberto (Springer, 2012)
The objective of this study was to describe the VNTR polymorphism of the mucin 1 gene (MUC1) in three Nelore lines selected for yearling weight to determine whether allele and genotype frequencies of this polymorphism were affected by selection for growth. In addition, the effects of the polymorphism on growth and carcass traits were evaluated. Birth, weaning and yearling weights, rump height, Longissimus muscle area, backfat thickness, and rump fat thickness, were analyzed. A total of 295 Nelore heifers from the Beef Cattle Research Center, Instituto de Zootecnia de Sertozinho, were used, including 41 of the control line, 102 of the selection line and 152 of the traditional. The selection and traditional lines comprise animals selected for higher yearling weight, whereas control line animals are selected for yearling weight close to the average. Five alleles were identified, with allele 1 being the most frequent in the three lines, especially in the lines selected for higher means for yearling weight. Heterozygosity was significantly higher in the control line. Association analyses showed significant effects of allele 1 on birth weight and weaning weight while the allele 3 exert significant effects on yearling weight and back fat thickness. Despite these findings, application of this marker to marker-assisted selection requires more consistent results based on the genotyping of a larger number of animals in order to increase the accuracy of the statistical analyses.
Keywords: Beef cattle; QTL; VNTR; Marker assisted selection; Zebu